Comparison of disk diffusion test and Etest for voriconazole and fluconazole susceptibility testing - Buchta, V; Vejsova, M; Vale-Silva, L A (Folia microbiologica, 2008)
The distribution for voriconazole and fluconazole susceptibility was determined by Etest and disk diffusion test in 143 clinical isolates. The majority of the strains of Aspergillus spp., Candida krusei, C. inconspicua, C norvegensis and Saccharomyces cerevisiae displayed resistance or decreased susceptibility to fluconazole in contrast to voriconazole. The absolute categorical agreement for voriconazole and fluconazole susceptibility results by the disk method and Etest was 90.5 and 74.8 % respectively. The error rate bounding analysis showed only 0.7 % of false susceptible results ( very major error) with voriconazole, but 2.8 % with fluconazole. Fluconazole can be used as a surrogate factor to predict voriconazole susceptibility but with lower reliability for susceptible-dose dependent and resistance category, especially in Candida glabrata isolates. The results of the disk method were not substantially influenced by the composition of media (Mueller-Hinton agar vs antimycotic Sensitivity Test agar), even if with the latter the results had fewer tendencies to produce false susceptibility of C.glabrata isolates to both of the triazole drugs. Disk test as well as Etest were shown to represent suitable methods for routine evaluation of susceptibility of clinical isolates of pathogenic fungi, including aspergilli, to fluconazole and voriconazole.
Keywords: houby; Triazoles; Disk Diffusion Antimicrobial Tests; flukonazol; Fluconazole; vorikonazol; Antifungal Agents; Microbial Sensitivity Tests; Pyrimidines; Drug Resistance, Fungal; Fungi; pyrimidiny; mykózy; triazoly; Humans; Voriconazole; fungální léková rezistence; Mycoses; kultivační média; mikrobiální testy citlivosti; lidé; antifungální látky; diskové difúzní antimikrobiální testy; Culture Media